MEMBANGUN BUDAYA LITERASI MELALUI MATA KULIAH BAHASA INDONESIA SEBAGAI MEDIA REVOLUSI MENTAL GENERASI PRODUKTIF - SALAM, EVELINA SATRIYA (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2017)
In the era of highly advanced communication as it is today, the role of sophisticated mobile phones and tablets replaced many of the roles of the book. As the result, students are more interseted in spending time with gadgets than reading and writing books. Moving from the phenomenom, the culture of literacy is sustained in the Indonesian language course. The Indonesian course as an MPK emphasizes the skills of using Indonesian as the national language and national in a good and correct way to master, apply, and develop science, technology, and art as the embodiment of love and nationality to the Indonesian language. The title raised in this paper is “ to build a culture of literacy through the Indonesian language as a medium of productive generation of mental revolution”. Importan issues that will be the author of lift, namely: How to build a culture of literacy through the Indonesian language as a medium of productive generation of mental revolution. The theory used, taht is mentally related to the mind. Mentality is related to the way of thinking. Indonesian language courses serve as a medium of mental revolution of productive generation. By presenting the substance of the term revolution of the study should be incorporated into the activities of using the Indonesian language through listening, speaking, reading and writing skills with focused academic writing skills so as to train or familiarize the mental revolution with the productive generation.